Analysis of human B‐cell responses following ChAd63‐MVA MSP1 and AMA1 immunization and controlled malaria infection. Issue 4 (April 2014) - Elias, Sean C.; Choudhary, Prateek; de, Simone C.; Biswas, Sumi; Collins, Katharine A.; Halstead, Fenella D.; Bliss, Carly M.; Ewer, Katie J.; Hodgson, Susanne H.; Duncan, Christopher J. A.; Hill, Adrian V. S.; Draper, Simon J.
Summary Acquisition of non‐sterilizing natural immunity to Plasmodium falciparum malaria has been shown in low transmission areas following multiple exposures. However, conflicting data from endemic areas suggest that the parasite may interfere with the induction of effective B‐cell responses. To date, the impact of blood‐stage parasite exposure on antigen‐specific B cells has not been reported following controlled human malaria infection (CHMI). Here we analysed human B‐cell responses in a series of Phase I/IIa clinical trials, which include CHMI, using candidate virus‐vectored vaccines encoding two blood‐stage antigens: merozoite surface protein 1 (MSP1) and apical membrane antigen 1 (AMA1). Previously vaccinated volunteers show boosting of pre‐existing antigen‐specific memory B‐cell (mBC) responses following CHMI. In contrast, unvaccinated malaria‐naive control volunteers developed an mBC response against MSP1 but not AMA1. Serum IgG correlated with the mBC response after booster vaccination but this relationship was less well maintained following CHMI. A significant reduction in peripheral MSP1‐specific mBC was observed at the point of diagnosis of blood‐stage infection. This was coincident with a reduction in peripheral blood B‐cell subsets expressing CXCR3 and elevated serum levels of interferon‐γ and CXCL9, suggesting migration away from the periphery. These CHMI data confirm that mBC and antibody responses can be induced and boosted by blood‐stage parasite exposure, in support of epidemiological studies on low‐level parasite exposure.